2002
DOI: 10.1034/j.1600-0528.2002.300307.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting dental sealants in school‐based programs: evaluation of an approach

Abstract: Several guidelines have been published in the United States to promote the appropriate use of sealants in both individual care and public health programs. Targeting sealants to children and teeth at high risk for dental caries has been accepted as a desirable strategy in school-based programs. However, there is little evidence to show that programs are complying with these guidelines. This report examined the extent to which sealants were targeted to high-risk children at 11 different school-based programs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…New York also selects geographic areas for its sealant program, the choice being based upon SES, demonstrated need, community interest, operational feasibility and ability to comply with the health department's rules and regulations (40). It differs from the Ohio program in that individual children are selected by the screening dentist as high risk on the basis of previous dental caries and deep pits and fissures, so this program combines some aspects of geographic targeting and individual selection.…”
Section: Prevention Targeted At the High‐risk Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…New York also selects geographic areas for its sealant program, the choice being based upon SES, demonstrated need, community interest, operational feasibility and ability to comply with the health department's rules and regulations (40). It differs from the Ohio program in that individual children are selected by the screening dentist as high risk on the basis of previous dental caries and deep pits and fissures, so this program combines some aspects of geographic targeting and individual selection.…”
Section: Prevention Targeted At the High‐risk Communitymentioning
confidence: 99%
“…It differs from the Ohio program in that individual children are selected by the screening dentist as high risk on the basis of previous dental caries and deep pits and fissures, so this program combines some aspects of geographic targeting and individual selection. What an evaluation showed, however, is that the criteria for selection of children and teeth were not well adhered to by the sealant team (40). This finding did not indicate a cavalier disregard for the carefully designed criteria on the part of the sealant team, but rather a necessary response to pressures from parents and school personnel that the sealant teams found difficult to resist.…”
Section: Prevention Targeted At the High‐risk Communitymentioning
confidence: 99%
“…In 2007, the number of sealed children was lower than in 2005-2006, partly explained by the diminished incentive for sealant service providers. However, the proportion of sealed children was still lower than that in other countries, for example, Slovenia with 62-100% (1988) [44], Ireland with 50-80% (1997) [45], and the United States with 51.1-88.0% and an extremely low coverage in one area of 41.0% (2002) [46].…”
Section: Emerging Trends In Oral Health Sciences and Dentistry 178mentioning
confidence: 99%
“…Similarly, since the resources for communitybased programs are usually limited, it has been recommended that these be targeted at populations or cornmunities in greatest need (5). For example, some public health sealant programs are targeted at lower socioeconomic schools with children with a previous history of caries and/or teeth with deep pits and fissures selected to receive sealants (11). It has also been suggested that school-based screening programs, which are intended to identify children in need of treatment and stimulate demand for dental care, should, as a matter of principle, be targeted at areas or groups where disease levels are high and/or access to dental care limited (12).…”
mentioning
confidence: 99%